Multi-trait genome-wide association study of opioid addiction: OPRM1 and beyond - Nathan Gaddis; Ravi Mathur; Jesse Marks; Linran Zhou; Bryan Quach; Alex Waldrop; Orna Levran; Arpana Agrawal; Matthew Randesi; Miriam Adelson; Paul W. Jeffries; Nicholas G. Martin; et al. (Scientific Reports, 2022)
Abstract Opioid addiction (OA) is moderately heritable, yet only rs1799971, the A118G variant in OPRM1, has been identified as a genome-wide significant association with OA and independently replicated. We applied genomic structural equation modeling to conduct a GWAS of the new Genetics of Opioid Addiction Consortium (GENOA) data together with published studies (Psychiatric Genomics Consortium, Million Veteran Program, and Partners Health), comprising 23,367 cases and effective sample size of 88,114 individuals of European ancestry. Genetic correlations among the various OA phenotypes were uniformly high (rg > 0.9). We observed the strongest evidence to date for OPRM1: lead SNP rs9478500 (p = 2.56 × 10–9). Gene-based analyses identified novel genome-wide significant associations with PPP6C and FURIN. Variants within these loci appear to be pleiotropic for addiction and related traits.